2017
DOI: 10.1007/s11356-017-0895-0
|View full text |Cite
|
Sign up to set email alerts
|

Set organic pollution as an impact category to achieve more comprehensive evaluation of life cycle assessment in wastewater-related issues

Abstract: For wastewater-related issues (WRI), life cycle assessment (LCA) is often used to evaluate environmental impacts and derive optimization strategies. To promote the application of LCA for WRI, it is critical to incorporate local impact of water pollutants. Organic pollution, a main type of water pollution, has not been given much consideration in current LCA systems. This paper investigates the necessity of setting a regionalized impact category to reflect the local impact of organic pollution. A case study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The most important advances in this topic have been made in China with several WWTP studies using Chinese normalization and weighting factors (Vera et al, 2015;Li et al, 2013;Zhao et al, 2018). Bai et al (2017) calculated specific Chinese normalization and weighting factors and obtained different environmental hierarchy for four discharge scenarios of a WWTP with activated sludge treatment when compared them with the results obtained with other non-Chinese normalization (CML (Guinée et al, 2001)) and weighting factors (BEES (Suh and Lippiatt, 2012)),…”
Section: Use Of Normalization and Weightingmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important advances in this topic have been made in China with several WWTP studies using Chinese normalization and weighting factors (Vera et al, 2015;Li et al, 2013;Zhao et al, 2018). Bai et al (2017) calculated specific Chinese normalization and weighting factors and obtained different environmental hierarchy for four discharge scenarios of a WWTP with activated sludge treatment when compared them with the results obtained with other non-Chinese normalization (CML (Guinée et al, 2001)) and weighting factors (BEES (Suh and Lippiatt, 2012)),…”
Section: Use Of Normalization and Weightingmentioning
confidence: 99%
“…EPA (Lippiatt, 2007) and EDIP 2003 (Hauschild and Potting, 2005)). Further development of general weighting factors and specific freshwater and terrestrial toxicity-based normalization indicators for China have been highlighted as main priorities for future WWT-related LCAs (Bai et al, 2017;Zhao et al, 2018;Li et al, 2013;Wang et al, 2015). To develop widely accepted weighting factors, the involvement of wide range of stakeholders is crucial.…”
Section: Use Of Normalization and Weightingmentioning
confidence: 99%
“…-LCA has also been used to address the environmental impacts as well as the benefits of supplementing, upgrading, and improving treatment processes [32,[36][37][38]. The obtained results indicated that LCA was powerful for optimizing the interaction among the operational parameters, thus facilitating access to the optimum decision [39][40][41][42]. A categorized literature review for LCA and wastewater treatment in accordance to LCA requirements by ISO 14040 [43] is provided in the next sections.…”
Section: China Pradel and Aissani [40] -mentioning
confidence: 99%
“…Cradle-to-gate: From the stage of untreated wastewater input to sludge treatment. Zhao, et al [39] 10,000 m 3 WWTP Pradel and Aissani [40] 1 kg WWTP…”
Section: The Scope and Functional Units In Wastewater Lcamentioning
confidence: 99%
See 1 more Smart Citation